On the Utility of Agronomic Monsoon Onset Definitions for Rainfed Aman Rice in Bangladesh - Han, Eunjin; Montes, Carlo; Krupnik, Timothy J.; Hussain, Sk Ghulam (2019)
The monsoon-season ‘aman' rice crop contributes approximately 40% of total rice production in Bangladesh, where per-capita rice consumption rates are among the highest in the world. Aman rice is primarily rainfed and relies largely on monsoon rainfall, more specifically monsoon onset and withdrawal. Aman rice farmers’ perception on the monsoon onset for the preparation of seedling does not necessarily coincide with typical meteorological onset definitions and varies with different locations. Therefore, agronomic definitions of monsoon onset, rather than meteorological definitions are needed in order to produce climate forecast information that can better support smallholder farmers’ decision making, and the definitions should be tailored for different regions. In this study, we analyzed historical daily rainfall from three regional weather stations across a north-south gradient in Bangladesh where rainfed transplanted rice is the dominant summer crop. We defined threshold numbers including the duration of the initial wet spell, amount of rainfall received during the initial wet spell, length of dry spell during the monsoon, and the maximum amount of rainfall received during the dry spell to develop a set of actionable and region-specific agronomic onset definitions. Because transplanting dates can affect crop productivity, a region-specific onset definition was evaluated in terms of crop model simulated attainable yields in comparison with the results of (a) conventional meteorological onset defined by the quantity of rainfall received and (b) static onset date definitions. When year-to-year varying agronomic onset definition was used predicted attainable yields were higher than those derived from traditional fixed onset date in the case of fully rainfed condition. If irrigation is available at the time of transplanting, however, simulated yields did not show distinctive differences between the different onset methods, underscoring how irrigation can be used as a climate-smart adaptive strategy to cope with monsoon variability. Our tailored agronomic definitions of monsoon onset can be used to assist rainfed rice farmers in choosing more favourable dates for the establishment of seedbeds and transplanting, especially when more advanced seasonal or sub- seasonal forecasts are available in addition to real-time and high-resolution rainfall monitoring.